2006
DOI: 10.1183/09059180.06.00009803
|View full text |Cite
|
Sign up to set email alerts
|

Costs of managing asthma as defined by a derived Asthma Control TestTMscore in seven European countries

Abstract: The present authors explored the relationship between asthma control status, as measured by a derived Asthma Control Test TM (ACT) score, and the utilisation and cost of healthcare in Europe. Data were derived from a European survey of asthma patients. Frequency of healthcare resource use was identified from the dataset and per-patient mean cost of asthma management estimated. Drug costs were not available. The ACT score was derived from questions in the survey identical or similar to the items comprising the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 17 publications
3
49
3
2
Order By: Relevance
“…These numbers are much higher than those in other studies (6-13.6%), 23,24 including a Vietnamese subgroup in an international study. 23 This may explain why the number of patients with severe asthma in this study is higher than in some other studies, 23,[25][26][27][28] while the rate of patients with controlled asthma in this study is also higher than that in other studies. 23,26,28 This result supports the concept that severity may not be an important index in asthma management.…”
Section: -9contrasting
confidence: 56%
See 2 more Smart Citations
“…These numbers are much higher than those in other studies (6-13.6%), 23,24 including a Vietnamese subgroup in an international study. 23 This may explain why the number of patients with severe asthma in this study is higher than in some other studies, 23,[25][26][27][28] while the rate of patients with controlled asthma in this study is also higher than that in other studies. 23,26,28 This result supports the concept that severity may not be an important index in asthma management.…”
Section: -9contrasting
confidence: 56%
“…23 This may explain why the number of patients with severe asthma in this study is higher than in some other studies, 23,[25][26][27][28] while the rate of patients with controlled asthma in this study is also higher than that in other studies. 23,26,28 This result supports the concept that severity may not be an important index in asthma management. 2 It is clear that 53% of patients in this study had moderate to severe asthma, but their asthma control is good because of their use of preventer therapy.…”
Section: -9contrasting
confidence: 56%
See 1 more Smart Citation
“…However, despite the availability of clinical practice guidelines and efficacious treatment options, [9][10][11][12][13][14] asthma is not well controlled for many patients, 15 and poorer asthma control is associated with higher costs and increased resource use. [15][16][17][18] In addition, large gaps still exist between the care recommended by guidelines and that actually provided, [19][20][21][22][23][24][25][26][27][28] and there is an inadequate focus on self-management. 29 A study from the Rand Corporation published in 2007 showed that adherence to 17 recommended ambulatory care indicators for children with asthma was only 46%.…”
mentioning
confidence: 99%
“…Some of these points are addressed in the articles in this issue of the European Respiratory Review; namely, the use of a validated self-administered measures to assess asthma control, and the potential economic benefit of achieving control of asthma [6][7][8][9].…”
Section: Ed Batemanmentioning
confidence: 99%